Evaluation of some African yam bean (Sphenostylis stenocarpa [Hochst. Ex A. Rich]) accessions for resistance to flower bud and pod rot diseases - C.G. Afolabi; O.M. Ogunsanya; O.I. Lawal (Current Plant Biology, 2019)
African yam bean (Sphenostylis stenocarpa) is an underutilized leguminous crop in the tropics with lofty nutritional value widely cultivated in the rural parts of Southern and Western Nigeria. This study was conducted to screen 20 accessions of AYB for resistance to these diseases, identify associated fungi and also determine the best cropping season to cultivate the crop with minimal infection. Field trials were conducted at the Teaching and Research Farm of the Federal University of Agriculture, Abeokuta during 2015/2016 cropping seasons (wet and dry seasons). The experiment was laid out in a randomized complete block design (RCBD) with three replications. During the wet season, flower bud rot and pod rot incidence were greater than 50 % among all accessions except in TSS 23 for pod rot. Disease severity of flower bud rot was not significantly (P ≥ 0.05) different among the AYB accessions, while the severity of pod rot was significantly (P ≤ 0.05) different among the AYB accessions. Eighteen accessions out of the 20 accessions assessed for resistance were found to be highly susceptible to flower bud infection, while 11 accessions showed resistance to pod rot infection during the wet season. However, all accessions did not produce flower buds and pods in the dry season. Seventeen fungi species belonging to thirteen genera were morphologically identified to be associated with the AYB flower bud and pod rot. This study provides baseline information for breeders on breeding for resistance to these diseases for disease management programme. Keywords: African yam bean, Accession, Disease, Fungi, Flower bud rot, Pod rot